Projeto implementação do gerenciamento matricial de despesas na AEL Sistemas S. A. - Rodrigues, Alberto da Silva (Universidade do Vale do Rio dos Sinos, 2013)
This Project Plan is related about the deployment of the Matricial Management of Expenses (GMD) into AEL Sistemas S.A. The project is justifiable because its importance, feasibility and opportunity on the costs reduction - currently existing in the company. The literature review reinforced concepts and definitions necessary to the right treatment regarding the matters about the Project product. (GMD). Thus, was used as base the best practices suggested by PMI through PMBOK – 4th edition, performing harmoniously the management of integration, scope, time, costs, quality, resources, communication, risks and acquisitions.
Keywords: AEL sistemas S.A.; Gerenciamento matricial de despesas; Orçamento matricial; Gerenciamento de projeto; Qualidade; Matricial management of expenses; Matricial budget; Project management; Quality